PERAN AGAMA DALAM MEMBENTUK MENTALITAS POSITIF PADA NARAPIDANA LANJUT USIA - Subroto, Mitro; Anasa, Eric Aditya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study explores the role of religion in shaping a positive mentality among elderly inmates. The increasing number of elderly prisoners raises concerns about their mental health and rehabilitation prospects. This research employs a qualitative approach, utilizing interviews and observations to gather data from elderly inmates in various correctional facilities. The findings reveal that religious practices significantly contribute to fostering hope, resilience, and a sense of community among these individuals. Moreover, religion serves as a coping mechanism, aiding in emotional regulation and promoting positive interactions with fellow inmates and staff. Ultimately, this study underscores the importance of integrating religious support into rehabilitation programs for elderly prisoners to enhance their mental well-being.Keywords: religion; positive mentality; elderly inmates; rehabilitation; mental health